2016
DOI: 10.1002/cjs.11284
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian regression models adjusting for unidirectional covariate misclassification

Abstract: In this article we consider unidirectional covariate misclassification, meaning that the direction of classification error is known. We investigate the identifiability of Bayesian regression models when a binary covariate is subject to unidirectional misclassification. In the Bayesian framework we consider whether knowledge of the direction of error suffices, so that adjustment for misclassification can be undertaken without any source of information on the magnitude of error. Although measurement error models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Here, we study statistical learning based on the conditional distribution of the misclassified response given the correctly measured covariate. Since the odds ratio is symmetric in the variables V and X , the problem has a similar nature to the binary response case discussed in Xia and Gustafson . Thus, it is not surprising to obtain the partial identification of the model.…”
Section: Binary Response Modelmentioning
confidence: 96%
See 2 more Smart Citations
“…Here, we study statistical learning based on the conditional distribution of the misclassified response given the correctly measured covariate. Since the odds ratio is symmetric in the variables V and X , the problem has a similar nature to the binary response case discussed in Xia and Gustafson . Thus, it is not surprising to obtain the partial identification of the model.…”
Section: Binary Response Modelmentioning
confidence: 96%
“…Note that the current model is similar to the binary response case studied in Xia and Gustafson in the sense that we are interested in assessing the association of a pair of binary variables with one of them subject to unidirectional misclassification. Treating the misclassified variable as a covariate, Xia and Gustafson showed that the model is partially identified when there is a binary response that is correctly measured. In the earlier paper, the identification is studied based on the conditional distribution of the correctly measured variable given the misclassified variable.…”
Section: Binary Response Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the problem of insurance misrepresentation, Xia and Gustafson (2016) is the first paper that studied the model identification and implementation when concerning the association between a response and a binary risk factor subject to misrepresentation. The paper used the term unidirectional misclassification from Gustafson (2014) for the type of measurement such as misrepresentation where the error occurs only in one direction that favors the respondent.…”
Section: Introductionmentioning
confidence: 99%
“…For all the earlier papers except for Gustafson (2014); Hahn et al (2016), the models possessed the identifiability, which enables us to perform statistical inference on all the model parameters without prior knowledge on the severity of misrepresentation. In the most recent paper concerning the problem of misrepresentation , the model from Xia and Gustafson (2016) was expanded for the purpose of predictive analytics on the misrepresentation risk, while including multiple risk factors with some of them subject to misrepresentation.…”
Section: Introductionmentioning
confidence: 99%